Brat Farrar - Tey, Josephine, 1896 or 7-1952. (London : Arrow Books, 2009)
A young English orphan who tries to pass himself off as the rightful heir in a horse-breeding family goes through a process of regeneration as he unfolds a murder mystery.
Adult.
Adult
Keywords: Impostors and imposture -- Fiction; Inheritance and succession -- Fiction; Impostors and imposture -- Fiction; Inheritance and succession -- Fiction; Mystery fiction; Midlands (England) -- Fiction; Midlands (England) -- Fiction; Detective and mystery stories